2002
DOI: 10.1016/s1359-835x(02)00031-3
|View full text |Cite
|
Sign up to set email alerts
|

Flexural and interlaminar shear strength properties of carbon fibre/epoxy composites cured thermally and with microwave radiation

Abstract: The ease of heating an epoxy resin with microwaves depends, among other factors, on the dielectric properties of its components at the frequency of the radiation used. The majority of the papers published on the microwave curing of reinforced epoxy resin composites have used widely available DGEBA type resins and amine hardeners such as 4,4'-diaminodiphenylsulphone (DDS). This paper investigates the use of two epoxy systems where the choice of resin and hardener was based on their measured dielectric loss fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(75 citation statements)
references
References 17 publications
5
70
0
Order By: Relevance
“…6c. The porosity increased from the surfaces towards the interior of the panel in this case and the void volume fraction in the center of the 1 It should be noted that the average laminate thickness was kj4.6 mm but kj0.5 mm in each surface were not included in the tomographic analysis. panel for unidirectional laminates was much higher than that found in multiaxial panels subjected to the same curing cycle.…”
Section: Void Orientation and Spatial Distributionmentioning
confidence: 84%
See 2 more Smart Citations
“…6c. The porosity increased from the surfaces towards the interior of the panel in this case and the void volume fraction in the center of the 1 It should be noted that the average laminate thickness was kj4.6 mm but kj0.5 mm in each surface were not included in the tomographic analysis. panel for unidirectional laminates was much higher than that found in multiaxial panels subjected to the same curing cycle.…”
Section: Void Orientation and Spatial Distributionmentioning
confidence: 84%
“…A prepreg raw sample of 25 mm in diameter and 4 plies in thickness was placed between the plates of the rheometer and subjected to an oscillatory shear strain of 0.05% and 1 Hz frequency while imposing a specified temperature cycle. The dynamic viscoelastic response of the composite prepreg in terms of the storage and loss moduli, C and G", respectively, is modified by the cross-linking reactions and the evolution of the complex viscosity if (modulus of real and imaginary parts) can be determined as if | C' + iC" (1) where m is the frequency of the oscillatory strain. The presence of the fibers in the prepreg increased storage component of the shear modulus and it was not possible to determine the gel point using the standard criterion for neat resins, i.e.…”
Section: Rheology and Thermal Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…<2%) are most often manufactured by the autoclave process [6][7][8]. Yet the composites industry is increasingly considering lower cost alternative processes such as hot-press molding because autoclave curing is expensive partially due to the high cost of the required equipment [8][9][10][11]. However, before hot-press molding or other out-of-autoclave processes can be implemented as an alternative to autoclave curing, techniques must be developed to allow for components to be fabricated with a comparable high quality.…”
Section: Introductionmentioning
confidence: 99%
“…But for carbon fiber reinforced composites, Nightingale and Day (2002) reported that the presence of carbon fibers in the composite may affect the penetrating depth of the microwave energy, because of the electrical conductivity and electromagnetic reflection of carbon fiber bundles. The experiments accomplished by Hunyar et al (2006) also showed that the anisotropic properties of composite materials may affect the temperature distribution.…”
Section: Introductionmentioning
confidence: 99%